HEMOGLOBINOPATHY IN BASRAH GOVERNORATE, CENTER STATISTICS AND NEW REGISTRY CHARACTERISTICS - Batool Falah Hassan; Gadeer Ali Lazim; Montazer Mansour Jassim; Maysaa Basim Obaid; Milad Mohammed Faleeh; Basim Abdulkareem.Alhijaj (PT. Antis International Publisher, 2024)
A retrospective study that had been conducted depending on the patients records and center data bases, concentration on the evidence of registering new cases of the disease categories, a total of 8721 patients had been registered most of them was of sickle cell diseases categories (sickle cell anemia, sickle/β+ and sickle/β0) of 5954 (68.26%), thalassemia syndromes (27.71%). 52.11% are males and 47.78% are females with a male: female ratio of 1.09, most of them are of below 18 years old 4741 (54.34%) with an adult group of 3972 (45.54%), one third of them were illiterates the rest were educated of different levels, only 6% reached higher education. 1817 different hemoglobinopathy patients was registered in Basrah during the last five years, 27.6% of them were registered during 2019 alone, 39.8% of them were homozygous sickle cell diseases while heterozygous (sickle/β+, sickle/β0) represented 33.0% of all registered cases, thalassemia syndromes (thalassemia major, thalassemia intermedia and α thalassemia) were only 27.0%. conclusions Basra governorate contain a large cohort of hemoglobinopathies patients on the national level and new case detection and registry is still significantly high for the last five years although premarital screening program did conducted recommendation a more correlational and comparable studies are to be conducted to highlight different variables of the disease-specific characteristics and an evaluation is to be conducted on evidence based way for the outcome of the currently conducted premarital screening program.